2019
DOI: 10.1002/app.48827
|View full text |Cite
|
Sign up to set email alerts
|

Thermosets resins prepared from soybean oil and lignin derivatives with high biocontent, superior thermal properties, and biodegradability

Abstract: A bio‐based monomer, methacrylated vanillyl alcohol (MVA), had been synthesized from vanillyl alcohol with methacrylate anhydride (MAA) via a solvent‐free, efficient method. The synthesis of MVA was confirmed by Fourier transform infrared (FTIR) and proton nuclear magnetic resonance (1H NMR). It was used to copolymerize with acrylated epoxidized soybean oil (AESO) to prepare a bio‐based resin (MVA–AESO). Excess MAA of MVA synthesis was further used to modify AESO with hydroxyl groups, generating (MVA–MAESO) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 46 publications
0
22
0
1
Order By: Relevance
“…Soil burial tests were done for three months. It was concluded that the resins had good biodegradability [28]. Chow, Tan and Ahmad prepared a bio-based thermoset resin by crosslinking an epoxidized soybean oil with an organic anhydride as a curing agent.…”
Section: Biodegradationmentioning
confidence: 99%
“…Soil burial tests were done for three months. It was concluded that the resins had good biodegradability [28]. Chow, Tan and Ahmad prepared a bio-based thermoset resin by crosslinking an epoxidized soybean oil with an organic anhydride as a curing agent.…”
Section: Biodegradationmentioning
confidence: 99%
“…Biodegradability of soybean oil‐based polymers could be predicted due to biodegradable triglyceride moieties, 36 through various RDs, cross‐linkers, and additives change the structure and density of cross‐links and affect biodegradability of polymers. About 15%–16% of thermally cross‐linked AESO and vanillin dimethacrylate thermosets degraded after a 3‐month soil burial test 37 . About 25% of 50% AESO blends with polyurethane acrylate biodegraded in the presence of the soft‐rot fungus Chaetomium globosum after 130 days of exposure, 38 while only about 6% of poly(ethylene glycol) diacrylate photocross‐linked with the same amount of AESO degraded in 24 days in phosphate buffer solution 39 .…”
Section: Introductionmentioning
confidence: 99%
“…About 15%-16% of thermally cross-linked AESO and vanillin dimethacrylate thermosets degraded after a 3-month soil burial test. 37 About 25% of 50% AESO blends with polyurethane acrylate biodegraded in the presence of the soft-rot fungus Chaetomium globosum after 130 days of exposure, 38 while only about 6% of poly(ethylene glycol) diacrylate photocross-linked with the same amount of AESO degraded in 24 days in phosphate buffer solution. 39 These moderate differences in the biodegradability of AESO-based polymers indicate not only the huge effect of comonomer, but also the type of the test used for determination of biodegradability on the obtained results.…”
Section: Introductionmentioning
confidence: 99%
“…Epoxidation is another suitable preliminary reaction for the insertion of acrylic moieties into the triglyceride backbone, which was the route adopted to prepare acrylated linseed oil and, in a further step, aza-Michael polymers using priamine 1071, amine-terminated poly(propyleneoxide)s (jeffamines), and meta-xylylenediamine as crosslinkers [ 45 ]. In a similar vein, acrylated epoxidized soybean oil was copolymerized with methacrylated vanillyl alcohol, which had been synthesized from vanillyl alcohol and methacrylate anhydride, to produce thermoset resins [ 46 ].…”
Section: Branched and Crosslinked Polymers Based On Pristine Or Chemically Modified Triglyceridesmentioning
confidence: 99%